PENGENALAN AKSARA JAWA UNTUK TUNA NETRA MILB BUDI ASIH MENGGUNAKAN MODEL GRAMBYANGAN - sanandita, ayunda dea (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2019)
Javanese script becomes local wisdom that can be learned by all Javanese people. everyone can learn one of these Javanese cultures, therefore, it is even studied by blind people. This study aims to introduce Javanese characters to children with disabilities, especially blind people as a manifestation of the preservation of Javanese culture and community service. Through the method of Grambyagan (fingering). This activity was carried out for 3 months in the framework of providing learning to students with Blindness at MILB Budi Asih Semarang. The introduction of whole Javanese characters to blind children with grambyangan models was conducted twice in one week. The initial meeting explained what Javanese script was, the second meeting began to introduce Javanese characters in the form of feelers as if they were blile writings called Denta Blille. In addition to raising the sound symbol with the habitual letters of the students, the original letters of the Javanese script were also conveyed on the board. As a result of this habituation, participants who had not known the form of Javanese script had become well acquainted. Increasing the ability of students measured by the Q chohran score formula produces an increase of 100% with a significance number of 0.005. The indication of this number is that the Javanese script learning activities using this learning model work well. Abstrak Aksara Jawa menjadi kearifan lokal yang dapat dipelajari oleh seluruh marsyarakat Jawa. semua orang dapat mempelajari salah satu kebudayaan Jawa ini, Oleh karena itu, bahkan dipelajari oleh masyarakat tunanetra. Penelitian ini bertujuan untuk mengenalkan aksara Jawa kepada anak penyandang disabilitas khususnya tunanetra sebagai wujud pelestarian budaya Jawa serta pengabdian kepada masyarakat. Melalui metode Grambyagan (meraba). Kegiatan ini dilakukan selama 3 bulan dalam kerangka memberi pembelajaran kepada siswa penyandang Tuna Netra di MILB Budi Asih Semarang. Pengenalan aksara Jawa utuh kepada anak tuna netra dengan model grambyangan dilakukan dua kali pertemuan dalam satu minggu. Pertemuan awal menjelaskan apa itu aksara Jawa, pertemuan kedua mulai memperkenalkan bentuk aksara Jawa dalam wujud alat peraba selayaknya tulisan blile yang disebut dengan istilah Denta Blille. Selain memunculkan simbol bunyi dengan huruf kebiasaan peserta didik, huruf asli dari aksara Jawa juga disampaikan pada papan tersebut. Hasil pembiasaan tersebut, peserta yang selama ini tidak mengenal bentuk aksara Jawa menjadi mengenal dengan baik. Peningkatan kemampuan peserta didik yang diukur melalui rumus Q chohran score menghasilkan peningkatan 100% dengan angka signifikansi 0,005. Indikasi angka tersebut, kegiatan belajaran aksara Jawa menggunakan model pembelajaran ini berhasil dengan baik.